Cultural infrastructure as an element of social integration and intercultural strengthening in the city of Tacna - Jiménez Salinas, Diana Gabriela (2014)
Objective: Develop and design the Architectural Project Cultural Center in the city of Tacna. As an element of social integration, while strengthening multiculturalism in the south of the country. Methodology: The research methodology for the thesis project is descriptive and explanatory various scientific methods such as Empirical and statistical methods that are fundamental to the development of the proposal is implemented. Results: In recent years the city of Tacna has experienced rapid growth due to its geographical location and commercial role which has led to constant migrations, hence its multiculturalism, why seek grant a cultural infrastructure for expressions . Conclusion: After the research on the customs and cultural expressions project called the Architectural arises "cultural infrastructure as an element of social integration and intercultural building in the city of Tacna"